The South American genus Quemedice Mello-Leitao (Araneae: Sparassidae): familial placement and taxonomic revision - Rheims, Cristina A.; Labarque, Facundo M.; Ramírez, Martín J. (Zootaxa, 2008)
The genus Quemedice Mello-Leitão, 1942 is revised. The female of the type species, Quemedice enigmaticus MelloLeitão, 1942 is redescribed and the male described and illustrated for the first time based on specimens from Argentina (Santiago del Estero province, near the type locality), central-western and southeastern Brazil (states of Minas Gerais, Mato Grosso and São Paulo). Quemedice piracuruca n. sp. is described based on male and female specimens from Colombia (Dept. Meta) and northern, northeastern and central-western Brazil (states of Piauí, Bahia and Minas Gerais). All specimens share the undisputed synapomorphy for Sparassidae, a soft dorsal trilobate membrane at the distal end of leg metatarsi, hence the genus is transferred to the family Sparassidae.